2020
DOI: 10.1097/rlu.0000000000002949
|View full text |Cite
|
Sign up to set email alerts
|

Tau Imaging in the 4-Repeat-Tauopathies Progressive Supranuclear Palsy and Corticobasal Syndrome

Abstract: Background and Objectives To evaluate tau PET using 11C-pyridinyl-butadienyl-benzothiazole 3 (11C-PBB3) in the 4-repeat (4R)-tauopathies progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS). Methods Retrospective analysis of 11C-PBB3 PET in 2, 7, and 2 patients with CBS, PSP, and Alzheimer dementia (AD), respectively. Normalized 11C-PBB3 uptake in clusters with significant hypometabolism on 18F-FDG-PET and corresponding atlas-based volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…This is consistent with CBD/S pathology which is hallmarked by asymmetric symptomology. In PSP patients, [11C]PBB3 uptake is heightened in the midbrain and thalamus compared to AD and CBS patients [67] . This finding is consistent with the neuropathological distribution of PSP-tau inclusions [9] , [68] .…”
Section: Imaging Pathological Taumentioning
confidence: 95%
See 1 more Smart Citation
“…This is consistent with CBD/S pathology which is hallmarked by asymmetric symptomology. In PSP patients, [11C]PBB3 uptake is heightened in the midbrain and thalamus compared to AD and CBS patients [67] . This finding is consistent with the neuropathological distribution of PSP-tau inclusions [9] , [68] .…”
Section: Imaging Pathological Taumentioning
confidence: 95%
“…When tested in CBS patients, [11C]PBB3 binding is observed extensively in the dorsal frontal, motor, and premotor cortices contralateral to the clinically more affected side [67] . This is consistent with CBD/S pathology which is hallmarked by asymmetric symptomology.…”
Section: Imaging Pathological Taumentioning
confidence: 99%
“…To the best of our knowledge, no study has yet attempted to assess the accuracy of PBB3, although the evidence so far imply a good accuracy for discrimination of HCs and clinically diagnosed AD patients and a different regional pattern of binding for non-AD neurodegenerative diseases [27,[47][48][49][50][51][52].…”
Section: Phase 2: Clinical Assay Development For Alzheimer's Disease Pathologymentioning
confidence: 99%
“…7,8 The most commonly affected areas include the putamen, globus pallidus, thalamus, subthalamic nucleus, midbrain (red nucleus and substantia nigra), dentate nucleus, parietal gray matter, and the frontoparietal white matter. [8][9][10] Differently from PSP, MSA is characterized by oligodendroglial cytoplasmic inclusions, which contain misfolded hyperphosphorylated α-synuclein, but not tau aggregates. 1 Although the patient's clinical manifestations (no ocular motor dysfunction) did not allow a definite diagnosis, the results of PET imaging using 3 different radiotracers suggested PSP.…”
mentioning
confidence: 99%
“…Tau PET imaging studies have consistently shown an increased tau accumulation in the brain of patients with PSP, corresponding to overrepresentation of tau isoforms containing 4-repeat domains in autopsy series. 7,8 The most commonly affected areas include the putamen, globus pallidus, thalamus, subthalamic nucleus, midbrain (red nucleus and substantia nigra), dentate nucleus, parietal gray matter, and the frontoparietal white matter. [8][9][10] Differently from PSP, MSA is characterized by oligodendroglial cytoplasmic inclusions, which contain misfolded hyperphosphorylated α-synuclein, but not tau aggregates.…”
mentioning
confidence: 99%